AB0285 First real life experience with certolizumab pegol in rheumathoid arthritis (ra) in latinamerica. (23rd January 2014) - Guzman, R.; Roa, G.; Rodriguez, W.; Cordoba, J.; Villalba, A.
Abstract : Background: Certolizumab pegol (CZP) is a novel TNF inhibitor, consisting of a humanized Fab' fragment fused to a 40-kd polyethylene glycol moiety with proved efficacy and safety in multiple RA clinical trials. Most pivotal clinical trials recruited patients from USA and Europe and therefore clinical experience in some developing countries including Latin America is limited. This is the first experience with CZP in daily clinical practice in Latin-American Country. Objectives: To describe the evolution and characteristics of the first Latin-American patients receiving treatment with CZP in clinical practice. Methods: 95 clinical records belonging to patients with active RA were reviewed; patients were treated with CZP in an autoimmune diseases specialized center in Colombia. Dosage scheme was 400 mg in weeks 0, 2, 4 followed by 400mg every 4 weeks. DAS28 score was recorded before treatment initiation with follow-ups at weeks 12 and 24. Mean change in DAS28 score, EULAR response and change in disease activity according to DAS28 score were calculated. Patients who discontinued treatment before week 24 were assigned to the non-responder group. Results: 95 patients were included in the analysis 76 were women, aged 21 to 80 years old (mean ±SD 54.8 ±13.2). Patients had used an average of 2.3 Synthetic Disease Modifying Anti Rheumatic Drugs, 23 patients had received one or more biological agents previously (24.47%). Mean baseline DAS28 score was 5.33±0.64; after 12 and 24 weeks the DAS28 was 2.9±0.99 and 2.77±1.24, with a mean change of -2.43±0.96 and -2.55±1.25 respectively. In 82 patients (86.32%) the decrease (>/=1.2 points) was clinically significant at week 24. At the end of the follow up period 69 participants (72.63%) showed a good EULAR (1 ) treatment response, 15 patients (15.79%) showed a moderate response and 11 were non-responders (11.58%). The Disease Activity changes are showed in table 1 . Six adverse events were reported which included a serious one (a recurrent urinary tract infection that required hospitalization and iv antibiotics). Conclusions: The first Latin-American patient's clinical evolution suggests an adequate effectiveness and safety profile for CZP. Results are consistent with findings from randomized clinical trials. References: Developmentand validationof the EuropeanLeagueAgainstRheumatismresponsecriteriafor rheumatoid arthritis. Comparison with the preliminary American College of Rheumatology and the World Health Organization/International LeagueAgainstRheumatismCriteria. Disclosure of Interest: None Declared